Treatment with Exogenously Added Catalase Alters CD8 T Cell Memory Differentiation and Function. Issue 4 (28th April 2022) - Aksoylar, Halil‐Ibrahim; Patsoukis, Nikolaos
Abstract: Cell‐based immunotherapy is a promising approach to cancer treatment. However, the metabolically hostile tumor microenvironment (TME) poses a major barrier to this therapeutic approach. Metabolic reprogramming may enhance T cell effector function and support longevity and persistence within the TME. Metabolic processes lead reactive oxygen species (ROS) production, which are mandatory mediators of signaling and immune cell functions, but detrimental when present in excess. Catalase (CAT) is an intracellular antioxidant enzyme that scavenges hydrogen peroxide (H2 O2 ), a central ROS member with a plethora of biological effects. H2 O2 is produced intracellularly and extracellularly, diffusing freely between the two compartments. In this study, it is found that scavenging extracellular H2 O2 by CAT supplementation has a major impact on the cell redox state, decreased intracellular ROS, but enhanced activation and altered memory differentiation. Under in vitro chronic activation conditions, CAT treatment favors CD8 T cells with less exhausted phenotype, increased activation and memory markers, and high bioenergetic capacity. Under in vitro acute activation conditions, CAT treatment selectively prevents differentiation transition from the stem cell memory/naive (TSCM /TN )‐ to the central memory (TCM )‐like phenotype, while enhancing activation and polyfunctionality. The study highlights the critical role of H2 O2 as a "hidden player" in T cell fitness and memory differentiation. Abstract : CD8 T cell activation results in excessive hydrogen peroxide (H2 O2 ) production freely diffusing intracellularly and extracellularly, promoting differentiation to effector memory (TEM ), decreased metabolic reserves, and low polyfunctionality. Activation in the presence of added catalase (CAT) lowers overall H2 O2, and sustains cells at the stem cell memory/naïve (TSCM /TN ) stage while allowing for enhanced activation, resulting in increased metabolic reserves and high polyfunctionality.